Estimación del efecto colegio en Colombia 1980-2009 (2012)
Based on the results from ICFES tests (Colombian equivalent of the American SATs) from 1980 to 2009, the study uses a hierarchical/multi-level analysis to provide an estimate of the school effect in each educational sector for three different tests. The results suggest that the public school effect has always been smaller than that of private schools in the last thirty years and that the effect on the mathematics section of the test is always smaller, regardless of the educational sector. They also indicate that since 2000 there has been a considerable drop in the coefficient, which could be related to the change in the tests that year. Lastly, an intertemporal analysis of score percentiles reveals that private schools have traditionally ranked higher than their public counterparts.